Influence of serum albumin on intracellular delivery of drug-loaded hyaluronan polymeric micelles - Nešporová, Kristina; Šógorková, Jana; Šmejkalová, Daniela; Kulhánek, Jaromír; Huerta-Angeles, Gloria; Kubala, Lukáš; Velebný, Vladimír (International journal of pharmaceutics, 2016)
Polymeric micelles are attractive drug delivery systems for intravenously administered nonpolar drugs. Although physical parameters like size, shape and loading capacity are considered as the most important for their efficiency, here we demonstrate that the effects of serum protein interaction and characteristics of loaded compound cannot be neglected during the micelle development and design of experimental set up. Polymeric micelles prepared from amphiphilic hyaluronic acid grafted with short (hexanoic) and long fatty acids (oleic) were tested after loading with two different hydrophobic models, Nile red and curcumin. The composition of micelles affected mainly the loading capacity. Both encapsulated compounds behaved differently in the in vitro cell uptake, which was also influenced by serum concentration, where serum albumin was found to be the primary destabilizing component. This destabilization was found to be influenced by polymeric micelle concentration. Thus, the chemical structure of micelle, the properties of non-covalently loaded substance and serum albumin/polymeric micelle ratio modulate the in vitro intracellular uptake of drugs loaded in nanocarriers.
Keywords: Albumin; Hyaluronan; HCT116 buňky; Cell uptake; Micelles; vazba proteinů; Drug Carriers; Polymers; Stability; lidé; HCT116 Cells; kyselina hyaluronová; Fatty acid; Polymeric micelle; sérový albumin; Hyaluronic Acid; intracelulární tekutina; Intracellular Fluid; Drug Delivery Systems; micely; polymery; nosiče léků; Serum Albumin; lékové transportní systémy; Cell Survival; viabilita buněk; HT29 Cells; Protein Binding; buňky HT-29; Humans